Faktor yang Memengaruhi Terjadinya Luka Tusuk Jarum Pada Perawat di Rumah Sakit Umum Daerah Sibuhuan Kabupaten Padang Lawas Tahun 2025: Penelitian - Ahmad Fauzi Nasution; Nuraini; Asriwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Needlestick injury (NSI) is a common occupational accident in hospitals and carries the risk of transmitting blood-borne pathogens. This study aimed to determine the factors influencing NSI among nurses at Sibuhuan Regional Hospital in 2025 using a cross-sectional design. The study population was 130 nurses with total sampling. Analysis used the chi-square test and logistic regression. The results showed that training (p<0.001), knowledge (p=0.038), use of PPE (p<0.001), and implementation of SOP (p=0.011) influenced NSI, with training as the most dominant factor (Exp(B)=16.437). This means that nurses who have never participated in training are 16.4 times more likely to experience NSI than those who have received training. It is recommended that Sibuhuan Regional Hospital conduct routine training, improve nurse education levels, and build a safe work culture to reduce the risk of occupational accidents.